Kepastian Hukum Kedudukan Kreditur Terhadap Debitur (PT Perseorangan) Dalam Undang-Undang Cipta Kerja - Lestari, Anak Agung Istri Laksmi; Dewi, Anak Agung Istri Ari Atu (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 8 No 02 (2023)DO - 10.24843/AC.2023.v08.i02.p13, 2023)
The purpose of this writing is to find out how the legal certainty of the creditor's position against the debtor (Individual Limited Liability Company) is in the Job Creation Law. This writing uses normative juridical methods or library research. The results of this study are legal certainty for creditors against Individual Limited Liability Companies as debtors who are in default in the Job Creation Law can be created if the Individual Limited Liability Company companies as debtors or partners of the company, for their negligence / mistakes in good faith are responsible for fulfilling their achievements as stated in Article 1338 of the Civil Code.